Key Competencies For Improving Local Governance. - United Nations Human Settlements Programme; Local Government and Public Service Reform;Initiative. (Nairobi : UN-HABITAT ; Budapest : Local Government and Public Service Reform Initiative)
"""HS/744/05E""--Vol. 1, p. [2] of cover. ""HS/745/05E""--Vol. 2, p. [2] of cover. ""HS/746/05E""--Vol. 3, p. [2] of cover. ""HS/747/05E""--Vol. 4, p. [2] of cover. 4 vols. contained in a portfolio. Includes bibliographical references. v.1. Quick guide -- v.2. Users guide -- v.3. Concepts and strategies -- v.4. Training tools."
Keywords: "LOCAL GOVERNMENT - NIGERIA - HANDBOOKS,;MANUALS, ETC.;LOCAL OFFICIALS AND EMPLOYEES - NIGERIA;HANDBOOKS, MANUALS, ETC.;NIGERIA - POLITICS AND GOVERNMENT - HANDBOOKS,"